A Dienyl Boronate‐Aryl Nitroso Ene Reaction Entry to C‐Pyrrolyl Nitrones and Subsequent Conversion to Isoxazolidines. Issue 16 (25th April 2018) - Eberlin, Ludovic; Macé, Aurélie; Batsanov, Andrei S.; Carboni, Bertrand; Whiting, Andrew
Abstract: A new cascade reaction to access C ‐pyrrolyl nitrones en route to isoxazolidines is reported; a process that involves four successive steps, the first key step being an ene‐reaction of a 3‐methyl‐1, 3‐dienylboronate ester with an aryl nitroso compounds to derive uncommon 1, 3‐dipoles which react with various alkenes to access isoxazolidines. The scope and mechanism of the cascade sequence is discussed. Abstract : A new cascade reaction to access C ‐pyrrolyl nitrones is reported. This process involves four successive steps; the first key step being an ene‐reaction of a 3‐methyl‐1, 3‐dienyl boronic ester with an aryl nitroso compound. The mechanism of the cascade sequence is discussed and the reactivity of these uncommon 1, 3‐dipoles towards various alkenes examined to access isoxazolidines.